Influence of type 2 diabetes mellitus on liver histology among morbidly obese individuals. A cross-sectional study - Cazzo, Everton (2016)
CONTEXT AND OBJECTIVE: Nonalcoholic fatty liver disease (NAFLD) has become a public health concern. It encompasses a wide spectrum of histological abnormalities and has close relationships with insulin re- sistance and type 2 diabetes mellitus (T2DM). This study sought to compare the histological alterations observed in morbidly obese individuals with and without T2DM who underwent Roux-en-Y gastric bypass. DESIGN AND SETTING: Cross-sectional study in a tertiary-level public hospital. METHODS: This was a cross-sectional study on 197 individuals who underwent gastric bypass surgery between 2011 and 2013. NAFLD was assessed through liver biopsies. T2DM was diagnosed through the International Diabetes Federation criteria. RESULTS: Non-diabetics presented significantly more biopsies without any histological abnormalities, regarding steatosis (42.6% versus 25.5%; P = 0.0400), fibrosis (60.6% versus 36.2%; P = 0.0042) and ste- atohepatitis (27.3% versus 12.8%; P = 0.0495), while diabetics presented significantly higher frequency of moderate forms of steatosis (36.2% versus 20%; P = 0.0307) and fibrosis (23.4% versus 4%; P = 0.0002). DISCUSSION: T2DM was associated with more advanced forms of NAFLD within the population studied. NAFLD has previously been correlated with severe forms of heart disease. CONCLUSION: Screening for and early detecting of NAFLD in high-risk populations are important for avoiding further development of severe forms and the need for liver transplantation.